2015
DOI: 10.1021/acs.biochem.5b00825
|View full text |Cite
|
Sign up to set email alerts
|

Thrombomodulin Binding Selects the Catalytically Active Form of Thrombin

Abstract: Human α-thrombin is a serine protease with dual functions. Thrombin acts as a procoagulant, cleaving fibrinogen to make the fibrin clot, but when bound to thrombomodulin (TM), it acts as an anticoagulant, cleaving protein C. A minimal TM fragment consisting of the 4th, 5th, and most of the 6th EGF-like domain (TM456m) has been prepared that has much improved solubility, thrombin-binding capacity, and anticoagulant activity over previous TM456 constructs. In the present work we compare backbone amide exchange o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 37 publications
1
38
0
Order By: Relevance
“…Previously published protease sensitivity and amide exchange studies consistently showed that the γ-loop is much more dynamic in apo-thrombin than in PPACK thrombin1536. Therefore it was not surprising that most of the NH cross peaks for γ-loop residues were missing, cross peaks for residues V138(174) in the β-strand leading into the γ-loop, and V158(199) and N159(200) in the β-strand exiting the γ-loop showed μs-ms motions in apo-thrombin (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Previously published protease sensitivity and amide exchange studies consistently showed that the γ-loop is much more dynamic in apo-thrombin than in PPACK thrombin1536. Therefore it was not surprising that most of the NH cross peaks for γ-loop residues were missing, cross peaks for residues V138(174) in the β-strand leading into the γ-loop, and V158(199) and N159(200) in the β-strand exiting the γ-loop showed μs-ms motions in apo-thrombin (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 97%
“…3). Recent HDXMS data showed a dramatic decrease in amide exchange in the N-terminus of the heavy chain upon PPACK-binding, however, some amides still exchanged within residues 16–33(37–44), indicating that part of this region is still exposed and/or dynamic15. The NMR results presented here now allow us to localize the change in dynamics to the most N-terminal residues 16–18 (37–39) of the thrombin heavy chain and to conclude that residues subsequent to these remain dynamic.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The TM activation of thrombin towards protein C cleavage was first performed by incubating the TM construct TM456m with purified human α-thrombin before adding protein C (Hematologic Technologies, Essex Junction, VT). TM456m was purified as previously described (14). Following a 20 min incubation with protein C, the thrombin was inactivated by addition of heparin-antithrombin-III, and the activated protein C was assayed by the addition of S-2366.…”
Section: Methodsmentioning
confidence: 99%
“…Five peptides corresponded to the 140s loop (residues 136–148, MH + 1401.58Da; residues 138–148, MH + 1169.53Da; residues 149–157, MH + 1169.63Da; residues 149–159, MH + 1355.73Da; residues 150–159, MH + 1192.67Da). The 140s loop is known as a very flexible loop in trypsin-like serine proteases, and it has been shown that binding of active site ligands allosterically reduces the conformational flexibility of this loop [ 24 ]. In good agreement with this notion, our results revealed that all five peptides covering the 140s loop showed decreased deuterium incorporation upon binding of EGR-cmk (Figs 3C and S1 ).…”
Section: Resultsmentioning
confidence: 99%